Increasing dietary crude protein levels attenuates the effects of caecotrope deprivation in growing rabbits - Salami, S. A.; Adelusi, O. O.; Isah, O. A.; Aderinboye, R. Y.; Ajayi, L. O. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The effect of caecotrope deprivation on growth, caecal metabolism and Volatile Fatty acid (VFA) production was studied in rabbits fed varying levels of dietary protein during a 42-days feeding trial. Fourty-eight mixed breed rabbits (average initial weight = 875±25 g) were divided into two groups viz; caecotrope consuming (CC) and caecotrope-deprived (CD) groups. Rabbits in the 2 groups were divided equally and assigned to 3 diets containing different crude protein (CP) levels (12, 15 and 18%) in a 2 × 3 factorial arrangement. The result revealed that increasing dietary CP improved (P<0.05) the proximate composition of the caecotrope. The live weight, weight gain, feed conversion ratio, nitrogen utilization and VFA production in CD rabbits fed diets containing 18% CP were comparable (P<0.05) with those of CC fed diets with 15% CP. Nitrogen utilization increased (P<0.05) following increasing dietary crude protein level. Molar proportions of acetate, butyrate, and propionate were higher (P<0.05) in CC rabbit compared to CD. Lactobaccilus acidophilus was isolated from the caecum of CC rabbits. It was concluded that caecotrope deprivation has detrimental effect on growth, nitrogen metabolism, VFA production and caecal bacteria and this effect can be attenuated by increasing the dietary protein level in growing rabbits.